Soluble catalysts for aprotic Li-O2 batteries - Gao, X (2017)
Aprotic lithium-air (O2) batteries have attracted significant interest due to their high theoretical specific energy. In an aprotic Li-O2 cell, O2 is reduced to form Li2O2 on discharge and the process is reversed on charge. Li2O2 is an insulating and insoluble solid, leading ultimately to poor cycling rates, low capacities and early cell death if it formed on the electrode surface. This is exacerbated by formation of Li2CO3 due to the cathode degradation with the presence of Li2O2 surface film. It is therefore desirable to form Li2O2 particles in solution, typically in batteries with high donor number electrolyte solvents that can dissolve the LiO2 intermediate. However, such solvents are more susceptible to nucleophilic attack by the reduced oxygen species, resulting in undesired side reactions. This project focuses on tackling the dilemma by promoting solution phase formation of Li2O2 in relatively stable low donor number solvents. Phenol was investigated as a protic additive that acts as a phase-transfer catalyst, dissolving Li2O2, avoiding electrode passivation and forming large particles of Li2O2. Discharge mediators were studied to shift O2 reduction to Li2O2 in solution via a new route that avoids the LiO2 intermediate, so that it increases the discharge potential, suppresses the growth of the Li2O2 thin film on the cathode surface, and thus postpones the cell death, increases the discharge capacity 80-100 fold and permits high discharge capacities with relatively high rates. However, Li2O2 particles growing via solution mechanism is disconnected from the electrode surface and therefore electronically isolated during charging, which requires redox mediators on charging. By combining discharge and charge mediators, the dual-mediator Li-O2 cell in this project was able to sustain cycling with capacities of 2 mAh cm-2areal at a rate of 1 mA cm-2areal over 50 cycles. By forming/decomposing Li2O2 in solution and avoiding high charge potentials, the carbon instability is significantly mitigated.